Clinical comparison of guided tissue regeneration, with collagen membrane and bone graft, versus connective tissue graft in the treatment of gingival recessions - Haghighati F; Akbari S (Tehran University of Medical Sciences, 2006)
Background and Aim: Increasing patient demands for esthetic, put the root coverage procedures in particular attention. Periodontal regeneration with GTR based root coverage methods is the most common treatment used. The purpose of this study was to compare guided tissue regeneration (GTR) with collagen membrane and a bone graft, with sub-epithelial connective tissue graft (SCTG), in treatment of gingival recession. Materials and Methods: In this randomized clinical trial study, eleven healthy patients with no systemic diseases who had miller's class I or II recession defects (gingival recession  2mm) were treated with SCTG or GTR using a collagen membrane and a bone graft. Clinical measurements were obtained at baseline and 6 months after surgery. These clinical measurements included recession depth (RD), recession width (RW), probing depth (PD), and clinical attachment level (CAL). Data were analyzed using independent t test with p<0.05 as the limit of significance. Results: Both treatment methods resulted in a statistically significant reduction of recession depth (SCTG=2.3mm, GTR=2.1mm; P<0.0001). CAL gain after 6 months was also improved in both groups (SCG= 2.5mm, GTR=2.1mm), compared to baseline (P<0.0001). No statistical differences were observed in RD, RW, CAL between test and control groups. Root coverage was similar in both methods (SCTG= 74.2%, GTR= 62.6%, P=0.87). Conclusion: Based on the results of this study, the two techniques are clinically comparable. Therefore the use of collagen membrane and a bovine derived xenograft may alleviate the need for connective tissue graft.